Endoscopic Anatomy of the Chorda Tympani: Systematic Dissection, Novel Anatomic Classification, and Surgical Implications. Issue 7 (August 2021) - Molinari, Giulia; Yacoub, Abraam; Alicandri-Ciufelli, Matteo; Monzani, Daniele; Presutti, Livio; Caversaccio, Marco; Anschuetz, Lukas
Abstract : Hypothesis: A transcanal endoscopic approach enables visualization of the variable course of the chorda tympani inside the middle ear. Background: The chorda tympani is the longest intrapetrous branch of the facial nerve. Despite having been investigated in several studies, a description of its tympanic tract from an endoscopic point of view is lacking in the literature. Methods: We performed transcanal endoscopic dissections of 44 human cadaveric head and ear specimens. The entry point of the chorda tympani into the middle ear was classified into four categories according to its location, and as covered or dehiscent according to its appearance. The chordal eminence (CE) was defined as absent, shallow, intermediate, prominent, or fused, based on its shape and extension. The relationship of the chorda tympani to adjacent bony and ligamental structures was assessed. Results: The tympanic tract of the chorda tympani was divided into three portions. The periannular segment was dehiscent in 54.5% of specimens, with type II being the most frequent entry point configuration (52.3%). In the interossicular segment, the nerve consistently passed lateral to the incus and medial to the malleus. The course of the intrapetrous segment was independent from the conformation of the tensor fold and supratubal recess. Conclusion: The transcanal endoscopic approach allows a detailed description of tympanic segment of the chorda tympani. Novel anatomic classifications of the chorda tympani and CE are proposed herein to highlight their possible surgical implications during otologic procedures. Abstract : Supplemental Digital Content is available in the text